Head-to-head comparison of length of stay, patients’ outcome and satisfaction in Switzerland before and after SwissDRG-Implementation in 2012 (Swiss Medical Weekly, 2014)
BACKGROUND: On 1 January 2012 Swiss Diagnosis Related Groups (DRG), a new uniform payment system for in-patients was introduced in Switzerland with the intention to replace a “cost-based” with a “case-based” reimbursement system to increase efficiency. With the introduction of the new payment system we aim to answer questions raised regarding length of stay as well as patients’ outcome and satisfaction. METHODS: This is a prospective, two-centre observational cohort study with data from University Hospital Basel and the Cantonal Hospital Aarau, Switzerland, from January to June 2011 and 2012, respectively. Consecutive in-patients with the main diagnosis of either community-acquired pneumonia, exacerbation of COPD, acute heart failure or hip fracture were included. A questionnaire survey was sent out after discharge investigating changes before and after SwissDRG implementation. Our primary endpoint was LOS. RESULTS: Of 1,983 eligible patients 841 returned the questionnaire and were included into the analysis (429 in 2011, 412 in 2012). The median age was 76.7 years (50.8% male). Patients in the two years were well balanced in regard to main diagnoses and co-morbidities. Mean LOS in the overall patient population was 10.0 days and comparable between the 2011 cohort and the 2012 cohort (9.7 vs 10.3; p = 0.43). Overall satisfaction with care changed only slightly after introduction of SwissDRG and remained high (89.0% vs 87.8%; p = 0.429). DISCUSSION: Investigating the influence of the implementation of SwissDRG in 2012 regarding LOS patients’ outcome and satisfaction, we found no significant changes. However, we observed some noteworthy trends, which should be monitored closely.